KESIAPAN ORANG TUA MENDAMPINGI BELAJAR ANAK SELAMA PANDEMI COVID-19 DI MADRASAH IBTIDAIYAH - Maya Ayu Purnama Sari; Rusma; Syarof Nursyah Ismail (Fakultas Tarbiyah, Universitas Ibrahimy, 2023)
Schools in Bali Learn Online (BDR) according to directions from the government due to the high Covid-19 cases. Learning activities carried out from home during the Covid-19 pandemic, especially at the SD/MI level, require the readiness of parents to accompany their children to learn at home. This study aims to determine the readiness of parents of MI Ma'arif Tabanan students in accompanying their children to learn during the Covid-19 pandemic. The approach used is descriptive quantitative type of survey research. Data collection is done through questionnaires, observation and documentation. The samples taken were 148 parents, then the data were analyzed using descriptive statistics, namely calculating the score or percentage of each indicator. The results showed that 40% of parents were ready to accompany their children to learn at home, 30% of parents were very ready, 29% of parent enough ready, and as much as 1% were not ready. The calculation are obtained through the results of measuring the five aspects including providing learning facilities, supervising children's learning activities at home, supervising the use of children's study time at home, monitoring difficulties faced by children in learning and helping children overcome difficulties in learning.